Altered Expression of Transfer-RNA-Derived Small RNAs in Human With Rheumatic Heart Disease - Yang, Zhao-yu; Li, Peng-fei; Li, Zhi-qing; Tang, Tao; Liu, Wei; Wang, Yang (Frontiers in Cardiovascular Medicine, 2021)
Rheumatic heart disease (RHD) remains a severe public health problem in developing countries. Atrial fibrillation (AF) is a medical complication of RHD. Although the understanding of the disease pathological process has advanced in recent years, the key questions need to be addressed. Transfer RNA–derived small RNAs (tsRNAs) are a novel type of short non-coding RNAs that have potential regulatory functions in various physiological and pathological processes. The present study used tsRNAs sequencing to investigate the relationship between RHD and atrial fibrillation (AF). Three paired myocardial papilla were taken from six rheumatic RHD patients with AF (3 cases) or without AF (3 cases) from January 2016 to January 2017 in Xiangya Hospital, Central South University. A total of 219 precisely matched tsRNAs were identified, and 77 tsRNAs (fold change > 2.0 and P < 0.05) were differently changed. Three tsRNAs (AS-tDR-001269, AS-tDR-001363, AS-tDR-006049) were selected and verified by qRT-PCR. The results of qRT-PCR were consistent with tsRNAs sequencing, suggesting the tsRNAs sequencing results were reliable. The bioinformatics analysis indicated that the target genes were abundant in transcription, DNA binding, and intracellular regulation. Furthermore, most of the genes were predicted to interplay with cytokine-cytokine receptors by KEGG analysis. Our findings uncover the pathological process of AF in RHD through tsRNAs sequencing. This study provides new ideas for future research on elucidating the mechanism of AF in RHD and offers potential new candidates for the treatment and diagnosis of AF in RHD.